SYIQAQ SEBAGAI ALASAN PERCERAIAN DI PENGADILAN AGAMA TULUNGAGUNG - Sukur, Mukhamad; Shobahah, Nurush (Ahkam: Jurnal Hukum Islam, 2021)
Marriage is an inner and outer bond based on the rules of religion and the laws between a man and a woman to constitute both inner and outer happy family. However, the high number of failing cases and divorce decisions in the Religious Court shows that there are various factors that might be a trigger to the failure of a marriage. A number of divorce cases data in Tulungagung Regency shows 225 divorce cases per month with an average of 20 lawsuits every day. The data in 2017 show that out of 3,114 divorce cases 2,150 cases were filed by women. The results of the analysis show that the high divorce rate is one of the dominance factor of dispute or quarrel (syiqoq) which was triggered by the following reasons; economy, one party leaves another party, continuous disputes, domestic violence, adultery, drunkenness and gambling. The high interest of the people of Tulungagung Regency who work as both Indonesian workers and female workers (TKI/ TKW) allegedly contributed to high divorce rate by the reason of syiqoq.